English language enhancement coaching for Baitul Hakim mosque youth at UIN Sayyid Ali Rahmatullah Tulungagung - Chojimah, Nurul; Sukarsono, Sukarsono (Universitas Muhammadiyah Malang, 2026)
This community service project aimed to improve the English proficiency of members of the youth organization at Baitul Hakim Mosque, UIN Sayyid Ali Rahmatullah Tulungagung, through a 16-session English short course. The program covered grammar focus, speaking, reading, and writing practices, using communicative and task-based approaches. Learning activities emphasized active participation, contextual language use, and collaborative tasks to create a supportive and engaging learning environment for mosque-based youth. Pre- and post-tests were administered, and the improvement was measured using Hake’s N-Gain formula. Results showed medium average N-Gain scores across all skill areas: grammar focus (0.325), speaking (0.36), reading (0.36), and writing (0.32). These findings indicate that the program effectively facilitated measurable improvement in participants’ English skills, with speaking and reading showing the highest gains, while writing remained the most challenging skill. The conclusion is that while the English enhancement coaching was effective in generating measurable improvements, particularly at the medium level, further serious efforts are needed to optimize instructional strategies. Besides, future implementations should consider extending the course duration, incorporating individualized learning paths, providing more intensive and sustained feedback—especially for writing—and leveraging a variety of engaging learning materials to better facilitate higher levels of language mastery among participants.